(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now a day economy is very important in construction industry. Reinforced concrete slab is familiar construction part use in modern building construction. Concrete is commonly use in all construction industry, concrete play and important role in construction industry. The quantity of concrete require in construction of floor system is more, its affect the economy of structure. Bubble deck slab system is best solution of this problem. Polypropylene ball is manufactured by using a plastic waste material. This polypropylene ball is used in the center part of slab it helps to reduce quantity of concrete. [2] Some amount of concrete is replaced polypropylene ball. Bubble deck slab is light in weight it also help to reduce the dead Load of slab and increasing efficiency.